2010
DOI: 10.1136/adc.2009.161158
|View full text |Cite
|
Sign up to set email alerts
|

Goals and options in keeping preterm babies warm

Abstract: More than 50 years after Silverman showed the association between temperature control and mortality, recent data again stress the importance of the thermal environment of the preterm infant. The goals of care are straightforward: maintain a normal body temperature, ensure a stable thermal environment and avoid cold stress; but the options to achieve them are many and less certain. There is a problem in defining a 'normal' temperature. A single measurement will tell nothing about whether the baby is using energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 39 publications
1
29
0
3
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10] The immature infant is at high risk of net heat loss because of a high surface area to volume ratio and increased evaporative fluid losses from the skin. 11 Strategies introduced to minimize heat loss include occlusive wrapping, exothermic warming mattresses, warmed humidified resuscitation gases, polyethylene caps, and higher delivery room (DR) temperatures. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Despite these interventions, hypothermia still occurs in a substantial number (10%-35%) of infants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10] The immature infant is at high risk of net heat loss because of a high surface area to volume ratio and increased evaporative fluid losses from the skin. 11 Strategies introduced to minimize heat loss include occlusive wrapping, exothermic warming mattresses, warmed humidified resuscitation gases, polyethylene caps, and higher delivery room (DR) temperatures. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Despite these interventions, hypothermia still occurs in a substantial number (10%-35%) of infants.…”
Section: Resultsmentioning
confidence: 99%
“…33 Investigators have evaluated different interventions, predominantly in VLBW infants ,1500 g or a GA ,30 weeks, to prevent heat loss, including using occlusive wrap, exothermic mattresses, warm caps, polyethylene caps, or heated humidified air or raising the OR temperature either singularly or in combination, with varied success. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Because of baseline data demonstrating frequent hypothermia in the larger premature infant, the combination approach of wrap, exothermic mattress, and cap was extended to all infants ,35 weeks old. Indeed, the greatest impact of the QI was noted in these infants.…”
Section: Discussionmentioning
confidence: 99%
“…In 1878, his local colleague Stéphane Tarnier, using a modified warming chamber for the rearing of poultry, found a decrease in neonatal death rate from 66 to 38% among infants with birth weights <2000 g. 67 Today, postnatal care devices (isolettes or infant warmers) combine the features of incubators and radiant warmer beds and have evolved with many features, including automated temperature and humidity regulations, 68 oxygen supplementation and light therapy. 11,69 Although beneficial in resource-replete settings, 70 utilization of their complex features requires electricity, concentrated oxygen supply, centralized suction and ongoing skilled maintenance. Priced at about US$15 000 to $36 000, 71 these devices are not affordable for most of the developing world.…”
Section: Diagnosismentioning
confidence: 99%
“…All the differences between methods were statistically significant (P<0,001). We never observed a difference between rectal and axillary/forehead temperature greater than 2°C, which could indicate 'cold stress' [20]. Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The agreement between the two methods could be due to the thermo-neutral environment where preterm infants were maintained. It has been found that preterm infants have a smaller core-surface temperature gradient because of their relative lack of thermal insulation by body fat [13,20].…”
Section: Discussionmentioning
confidence: 99%